Decreased somatic hypermutation induces an impaired peripheral B cell tolerance checkpoint - Cantaert, Tineke; Schickel, Jean-Nicolas; Bannock, Jason M.; Ng, Yen-Shing; Massad, Christopher; Delmotte, Fabien R.; Yamakawa, Natsuko; Glauzy, Salome; Chamberlain, Nicolas; Kinnunen, Tuure; Menard, Laurence; Lavoie, Aubert; et al. (The Journal of clinical investigation, 2016)
Patients with mutations in AICDA, which encodes activation-induced cytidine deaminase (AID), display an impaired peripheral B cell tolerance. AID mediates class-switch recombination (CSR) and somatic hypermutation (SHM) in B cells, but the mechanism by which AID prevents the accumulation of autoreactive B cells in blood is unclear. Here, we analyzed B cell tolerance in AID-deficient patients, patients with autosomal dominant AID mutations (AD-AID), asymptomatic AICDA heterozygotes (AID+/-), and patients with uracil N-glycosylase (UNG) deficiency, which impairs CSR but not SHM. The low frequency of autoreactive mature naive B cells in UNG-deficient patients resembled that of healthy subjects, revealing that impaired CSR does not interfere with the peripheral B cell tolerance checkpoint. In contrast, we observed decreased frequencies of SHM in memory B cells from AD-AID patients and AID+/- subjects, who were unable to prevent the accumulation of autoreactive mature naive B cells. In addition, the individuals with AICDA mutations, but not UNG-deficient patients, displayed Tregs with defective suppressive capacity that correlated with increases in circulating T follicular helper cells and enhanced cytokine production. We conclude that SHM, but not CSR, regulates peripheral B cell tolerance through the production of mutated antibodies that clear antigens and prevent sustained interleukin secretions that interfere with Treg function.